PENGARUH TINGKAT KESADARAN GIZI KELUARGA TERHADAP STATUS GIZI BAYI (0-11 BULAN) DI KECAMATAN PURWOKERTO SELATAN KABUPATEN BANYUMAS - Erna Kusumawati; Dyah Umiyarni Purnamasari (Kesmas Indonesia, 2010)
KADARZI program had goal to improve family wmpowerment by approach and change its nutrition practice to solve nutrition problems. South purwokerto subdistrict has 50,15% family that has been not kadarzi and has unsatisfied nutritional status. This research has objective to analisis the level KADARZI to nutritional status in infants (0-11 mounth) at south purwokerto subdistrict. This reasech was a survey study by using crossetional study the variables where practice of KADARZI : growth monitoring infants, breastfeeding comsumption of salt iodine, food combination, comsumption of supplement (indefendent variables) and nutrition status in infant (dependent variable). The population were 777 family and 86 family of sampling. Research resuld showed that ther was significant influence between exclusive breastfeeding and nutritional status (p velue: 0,007), variables that no significant influence were growth monitoring (p value: 0,184), food combination (p value: 0,342), comsumption salt iodine (p value: 0,609) and comsumption of nutrition supplement (p value: 0,307). Suggestion to get promotion and motivation to mother for exclusive breastfeeding.